Current chance of unprecedented monsoon rainfall over India using dynamical ensemble simulations. (3rd September 2020) - Jain, Shipra; Scaife, Adam A; Dunstone, Nick; Smith, Doug; Mishra, Saroj K
Abstract: In the past, India has suffered severe socio-economic losses due to recurring floods and droughts during boreal summer (June–August). In this analysis, we estimate the chance of extreme summer rainfall, i.e. flood and drought over India for the present climate using the UNprecedented Simulated Extremes using ENsembles (UNSEEN) method. This is the first application of the method to the hindcasts from multiple coupled atmosphere-ocean models. We first test individual models against the observed rainfall record over India and select models that are statistically indistinguishable from observations. We then calculate the chances of floods, droughts and unprecedented rainfall using 1669 realizations of summer precipitation from the selected set of models. It is found that the chance of drought is larger than the chance of flood in the present climate. There is a clear El Niño (La Niña) signal in dry (wet) summers and the occurrence of more frequent and intense droughts than floods in both models and observations is partly due to El Niño Southern Oscillation phase asymmetry. The chances of record-breaking drought and flood are 1.6% and 2.6%, respectively. There is also an estimated chance that a 30% rainfall deficit could occur around once in two centuries, which is far beyond the record deficit over India.